The leadership characteristics of the preceptor in selected clinical practice settings in Botswana - Dube, A; Jooste, K (Curationis (Pretoria), 2006)
A non-experimental, explorative, descriptive, quantitative study was undertaken. The purpose was to explore and describe the views of preceptors and preceptees regarding the fulfilment of the role of the preceptor in selected clinical nursing practice settings in the Botswana context. The study included 72 preceptors and 200 nursing students/preceptees who voluntary agreed voluntarily to participate in the study. A questionnaire was used to collect data, which was analyzed by using descriptive and inferential statistics. The findings of this study indicated that the preceptor lacked leadership characteristics in the accompaniment of the preceptee. These constraints included the lack of desirable characteristics such as intellectual, emotional, physical and other traits that are common to all good leaders. Recommendations were stated for improvements in selecting preceptors with certain leadership skills for the clinical practice settings. The limitations of this study were highlighted.